PENGARUH GAYA KEPEMIMPINAN, PENGALAMAN KERJA, DAN KOMUNIKASI INTERNAL TERHADAP KINERJA KARYAWAN PT. BANK BTN SYARIAH KOTA BANDA ACEH - Tuwisna Tuwisna; Tarmizi Gadeng; Sulfitra Sulfitra; Rizki Murzani (Universitas Muhammadiyah Aceh, 2022)
This research was conducted to examine the effect of leadership style, work experience, and internal communication on employee performance at PT. Bank BTN Syariah Banda Aceh city. Data collection techniques using a questionnaire. The method used is the associative method which aims to determine the effect or relationship between two or more variables. Determination of the sample using a saturated sample technique where all the population is sampled. The sample used in this study were 64 employees at PT. Bank BTN Syariah Banda Aceh city and willing to be a respondent. The results showed that leadership style partially positive and significant effect on employee performance at PT. Bank BTN Syariah Banda Aceh city. Work experience partially positive and significant effect on employee performance at PT. Bank BTN Syariah Banda Aceh city. Internal communication partially positive and significant effect on employee performance at PT. Bank BTN Syariah Banda Aceh city. Leadership style, work experience, and internal communication simultaneously have a positive and significant effect on employee performance at PT. Bank BTN Syariah Banda Aceh city. Employee performance improvement is determined by leadership style, work experience and internal communication. The better the leadership style provided and the more experienced the employees and the better the internal communication at PT. Bank BTN Syariah Banda Aceh city, the greater the opportunity for PT. Bank BTN Syariah Banda Aceh city to improve the performance of its employees.